2016
DOI: 10.2217/imt.16.3
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Immunopathogenesis and Immunotherapy

Abstract: Worldwide there are over 248 million chronic carriers of HBV of whom about a third eventually develop severe HBV-related complications. Due to the major limitations of current therapeutic approaches, the development of more effective strategies to improve therapeutic outcomes in chronic hepatitis B (CHB) patients seems crucial. Immune activation plays a critical role in spontaneous viral control; therefore, new modalities based on stimulation of the innate and adaptive immune responses could result in the reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 164 publications
0
15
0
Order By: Relevance
“…The majority of studies have shown that there is no significant difference between the frequency of pDCs and mDCs between CHB patients and healthy controls. 15,28,32,33 However, some exceptions exist, some studies showed reduced frequencies of pDC in patients with CHB. [34][35][36] In one study, nucleotide analogue antiviral therapy restored the number of circulating pDC, 34 while another study reported that this treatment improved the number of mDCs, but not of pDCs.…”
Section: Pdcs and Hbvmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of studies have shown that there is no significant difference between the frequency of pDCs and mDCs between CHB patients and healthy controls. 15,28,32,33 However, some exceptions exist, some studies showed reduced frequencies of pDC in patients with CHB. [34][35][36] In one study, nucleotide analogue antiviral therapy restored the number of circulating pDC, 34 while another study reported that this treatment improved the number of mDCs, but not of pDCs.…”
Section: Pdcs and Hbvmentioning
confidence: 99%
“…The majority of studies show that TLR-9 mediated IFN-α production by pDCs of CHB patients is reduced as compared with that of healthy individuals. 15,31,37,40 Besides, TLR9 protein expression levels are remarkably decreased in peripheral blood mononuclear cells (PBMC) from CHB patients reflecting dramatic shut down of TLR9 in both pDC and B cells. 31 In spite of the inhibitory effect of HBV/HBsAg on TLR9 stimulation, HBV/HBsAg exerts no effect on TLR7-mediated IFN-α secretion.…”
Section: Pdcs and Hbvmentioning
confidence: 99%
See 2 more Smart Citations
“…The HBV is now a challenging global health related issue especially in the Asia Pacifi c region. Both the host and the viral factors are mainly said to be associated to the pathogenesis of HBV infection, which are known to contribute to the clinical outcomes of chronic HBV infection Liver diseases and liver cancer shows a marked worldwide geographic and ethnic distribution (Shields and Harris, 1991, Lee et al,1997, Liu, Chen and Lai, 2003and Golsaz and Shokri 2016.…”
Section: Introductionmentioning
confidence: 99%